Early results using a biodegradable magnesium screw for modified chevron osteotomies. Issue 12 (7th April 2016) - Plaass, Christian; Ettinger, Sarah; Sonnow, Lena; Koenneker, Soeren; Noll, Yvonne; Weizbauer, Andreas; Reifenrath, Janin; Claassen, Leif; Daniilidis, Kiriakos; Stukenborg‐Colsman, Christina; Windhagen, Henning
ABSTRACT: This is the first larger study analyzing the use of magnesium‐based screws for fixation of modified Chevron osteotomies in hallux valgus surgery. Forty‐four patients (45 feet) were included in this prospective study. A modified Chevron osteotomy was performed on every patient and a magnesium screw used for fixation. The mean clinical follow up was 21.4 weeks. The mean age of the patients was 45.5 years. Forty patients could be provided with the implant, in four patients the surgeon decided to change to a standard metallic implant. The AOFAS, FAAM and pain NRS‐scale improved markedly. The hallux valgus angle, intermetatarsal angle and sesamoid position improved significantly. Seven patients showed dorsal subluxation, rotation or medial shifting of the metatarsal heads within the first 3 months. One of these patients was revised, in all others the findings were considered clinically not significant or the patients refused revision. This study shows the feasibility of using magnesium screws in hallux valgus‐surgery. Surgeons starting with the use of these implants should be aware of the proper handling of these implants and should know about corrosion effects during healing and its radiographic appearance. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:2207–2214, 2016.